Study and Review on BDAAS in OWL-S Based Secure Clouds Using Bigdata - Jyosna, Koppala; Prakash, N Bhanu (International Journal of Computer Sciences and Engineering, 2025)
Development of Information Technology moves all business associations to advanced business. Associations treat information as a benefit since it tends to be characterized as a gathering of put away realities that are available to translation and control for authoritative forms. Value-based, social, portable, cloud and sensor information accessible now a days offer tremendous possibilities in hierarchical handling. Database, enormous information and business knowledge innovations collaborate to make another business innovation. The advancements are progressively getting to be information driven. The accessibility of information procurement, accumulation and putting away stages are turning into a need since focal capacity of information in a database lessens information repetition, information disconnection, and information irregularity and permits for information to be shared among clients of the information. These extensive datasets, prominently known as Big Data, are hard to oversee utilizing conventional processing advancements. Distributed computing Cloud processing kills the need to keep up costly figuring equipment, devoted space, and programming. In this exploration paper the specialist examinations the execution of Big Data as an administration in cloud conditions and distinguished the elements to be considered actualizing Big Data-as-a-Service on the cloud.